2019
DOI: 10.14429/djlit.39.3.14354
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Legal Issues Related to Libraries among Library Professionals of Gujarat

Abstract: The awareness of legal issues related to libraries among library professionals in Gujarat is discussed in the current study. The research is based on an online survey of library professionals of Gujarat. The major findings of the survey reveal that there is an acute need to improve the awareness and knowledge about legal issues and legal provisions among LIS professionals in Gujarat. The results also show that educational background, experience, or designation have no correlation with leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 11 publications
0
5
1
Order By: Relevance
“…Secker et al (2019), after giving a detailed account of experiences of copyright literacy in Norway, Turkey, Romania, the UK and Sweden, conclude that the present situation of the librarians in these regions in respect of copyright literacy is not up to the mark. Patel and Hanumappa’s (2019) study found that LIS professionals’ level of understanding about copyright was not ideal, although they were somewhat aware of the issues involved. According to Fernández-Molina et al (2017), comparatively, librarians have a higher degree of awareness of the validity of copyright, Creative Commons licences and the public domain.…”
Section: Literature Reviewmentioning
confidence: 92%
See 3 more Smart Citations
“…Secker et al (2019), after giving a detailed account of experiences of copyright literacy in Norway, Turkey, Romania, the UK and Sweden, conclude that the present situation of the librarians in these regions in respect of copyright literacy is not up to the mark. Patel and Hanumappa’s (2019) study found that LIS professionals’ level of understanding about copyright was not ideal, although they were somewhat aware of the issues involved. According to Fernández-Molina et al (2017), comparatively, librarians have a higher degree of awareness of the validity of copyright, Creative Commons licences and the public domain.…”
Section: Literature Reviewmentioning
confidence: 92%
“…The findings of the studies by Arias Coello et al (2020) and Saunders and Estell (2019) reveal that, in Spain and the USA, the majority of LIS students preferred to use websites, books, articles and librarians to learn about copyright and related rights. Patel and Hanumappa (2019) examine copyright and its legal aspects, and discuss the many dimensions of copyright literacy, concluding that the majority of their respondents consulted e-learning sources, journals and their professional counterparts to gain knowledge of legal issues. Gastinger and Landøy (2019), in a study on the copyright literacy of LIS students in Norway, found that they sought copyright-related advice from websites, books and articles.…”
Section: Sources Of Information About Copyright and Related Rightsmentioning
confidence: 99%
See 2 more Smart Citations
“…First of all, the researchers studied the previous literature to understand the censorship issues, the role of the librarians in dealing with these issues, the awareness and preparedness of the librarians in this regard and scales used to measure the awareness and preparedness of the CLs. In the educational background (for librarians), several scales were established to quantify the awareness (Patel and Hanumappa, 2019) and the preparedness of librarians (Cooper, 2016) separately. However, these scales cannot be directly applied to measure the awareness and preparedness of CLs regarding censorship.…”
Section: Censorship Issuesmentioning
confidence: 99%